Pengaruh Model Pembelajaran Treffinger Terhadap HOTS Peserta Didik dalam Mata Pelajaran IPS di SMP Negeri 1 Gombong - Sadiyah, Nur Fitriani; Ginanjar, Asep (Sosiolium: Jurnal Pembelajaran IPS, 2020)
The birth of the 2013 curriculum requires an increase in the thinking skills of students. The purpose of this study was to determine the effect of the Treffinger learning model on HOTS in social studies subjects at SMP Negeri 1 Gombong. The method used in this research is quantitative. The results of this study are (1) The implementation of learning using the Treffinger learning model at SMP N 1 Gombong consists of three stages, namely basic tools, practice with processes, and working with the real problems. The learning model (2) Treffinger has an effect that increases the HOTS of students at social studies learning. This is known from the value of sig. = 0.000 <0.05 with t_hitung = -13.763. HOTS using the Treffinger learning model has a higher effect than learning using the conventional learning model. (3) There are obstacles in learning using the Treffinger learning model, namely differences in the abilities of each student in readiness to receive the material given.